WhatsApp is an effective tool for obtaining second opinion in oral pathology practice. (10th November 2016) - Sarode, Sachin C.; Sarode, Gargi S.; Anand, Rahul; Patil, Shankargouda; Unadkat, Hemant
Abstract : Background: The aim of this study was to find out the efficacy of WhatsApp application for obtaining second opinion on histopathological diagnosis in oral pathology practice. Methods: A total of 247 cases comprising of 34 different oral pathologies were photomicrographed using smartphone cameras through compound microscopes and sent for second opinion diagnosis (SOD) to 20 different oral pathologists using WhatsApp. Results: Of 4795 (97.06%) total second opinion received, correct SOD were received for 4710 (98.22%) cases. Hundred percent times correct SOD was received for lesions including adenomatoid odontogenic tumor, keratinizing cystic odontogenic tumor, odontome, and dentigerous cyst. Lesions such as myoepithelial carcinoma, osteosarcoma, fibrosarcoma, and intravascular papillary endothelial hyperplasia received less percentage of correct SOD (85.71–75.75%). Correct SOD was obtained for variants of ameloblastoma (99.01%), grading of epithelial dysplasia (87.54%), and squamous cell carcinoma (95.26%). A positive correlation was observed between correct SOD and age ( P = 0.0143) and experience ( P = 0.0189) of the pathologist. The time taken for giving second opinion by the pathologists ranged from 81.98 ± 32.89 to 90.72 ± 38.88 min. Conclusion: Smartphone camera is a handy and efficient tool in capturing photomicrographs from the compound microscope. Transfer of such photomicrograph via WhatsApp is an effective and convenient approach in procuring second opinion on histopathological diagnosis of oral pathologies.